EFFECT OF SUPERVISION AND QUALITY OF SERVICE ON EMPLOYEE WORK PRODUCTIVITY AT THE HARBORMASTER AND PORT AUTHORITY OFFICE CLASS III KIJANG - Rachman, Abd.; Paradila Putri, Inggerit; Indrayani, Indrayani; Ngaliman, Ngaliman (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This study is intended to analyze the work productivity of employees at the Harbormaster and Port Authority Office Class III Kijang. By using the variables of supervision and service quality to analyze the effect on the employee's work productivity. The population in this study were employees at the Harbormaster and Port Authority Office Class III Kijang. The samples taken in this study were 30 respondents. Data collection was used by the questionnaire method, namely by providing a list of questions to the respondents. The results of this study indicate that supervision and service quality affect the work productivity of employees at the Harbormaster and Port Authority Office Class III Kijang where the R value is 0,683(68.3%). While the R-square coefficient = 0.467 so that the coefficient of determination (R2) = 46.7% can be calculated. For the partial test (t test) it was found that the supervision was accepted, with a significant value of 0.035 < 0.05, the quality of service was accepted, so that a significant value of 0.000 < 0.05 was obtained. While the simultaneous test is obtained Fcount > Ftable or 11.807 > 3.34 and Fsig level 0.000 < 0.05 then Ha accepted.